2012
DOI: 10.1007/s11019-012-9382-z
|View full text |Cite
|
Sign up to set email alerts
|

Advance medical directives: a proposed new approach and terminology from an Islamic perspective

Abstract: Advance directives are specific competent consumers' wishes about future medical plans in the event that they become incompetent. Awareness of a patient's autonomy particularly, in relation to their right to refuse or withdraw treatment, a right for the patient to die from natural causes and interest in end of life issues were among the main reasons for developing and legalizing advance medical directives in developed countries. However, in many circumstances cultural and religious aspects are among many facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…[31] In Islamic countries such as Iran, there is no advance directives regarding end of life medical decisions. [32] Based on Islamic law, "decisions about life belong to Allah, not to the person himself and documents to preserve or end personal life are not recognized" (Babgi, 2009). Of course, Islamic idea of humanity provides a provisional framework in which advance directive can generally be considered legitimate.…”
Section: Discussionmentioning
confidence: 99%
“…[31] In Islamic countries such as Iran, there is no advance directives regarding end of life medical decisions. [32] Based on Islamic law, "decisions about life belong to Allah, not to the person himself and documents to preserve or end personal life are not recognized" (Babgi, 2009). Of course, Islamic idea of humanity provides a provisional framework in which advance directive can generally be considered legitimate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Muslims are permitted to refuse treatment in the context of incurable diseases and to not have undesired treatments given to them. 43…”
Section: Health Decision Making and Advance Care Planningmentioning
confidence: 99%
“…Although the concept of advance directives is deeprooted in Islamic teaching, it is seldom practised in the setting of end of life health care planning among Arab patients, or even among other Muslims (5). Among Saudi citizens there is a strong belief that open discussion of serious illness may cause unnecessary depression or anxiety to the patient (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Physicians often utilize technical terms to minimize or obscure the seriousness of the disease and its prognosis (4,5). Some investigators concluded that implementing a programme to increase physician opportunity to discuss end of life care with their patients, and improve residents' confidence in leading discussions regarding advance care directives, led to more patients expressing interest in talking about their wishes (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation